Fibrinogen Šumperk II: dysfibrinogenemia in an individual with two coding mutations - Kotlín, Roman; Suttnar, Jiří; Cápová, Irena; Hrachovinová, Ingrid; Urbánková, Marie; Dyr, Jan Evangelista (American journal of hematology, 2012)
Fibrinogen—a 340-kDa glycoprotein—plays a crucial role in blood coagulation, platelet aggregation, wound healing, and other physiological processes. A mutation in fibrinogen may lead to congenital dysfibrinogenemia,a rare disease characterized by the functional deficiency of fibrinogen. About 580 cases of abnormal fibrinogens have been reported worldwide; thereof 335 cases in the fibrinogen Aa chain[1]. To our knowledge, only five cases of abnormal fibrinogens with two mutations [2–6] and one case of two different mutations in the same family [7] have been described earlier. A 52-year-old female was examined for bleeding. Routine hemostasis screening resulted in a diagnosis of dysfibrinogenemia. Functional testing revealed prolonged fibrin polymerization, prolonged lysis of the clot, abnormal fibrin morphology,and fibrinopeptides release. Genetic analysis showed two heterozygous nonsense mutations—previously described mutation AaGly13Glu and a novel mutation Aa Ser314Cys. The mutation Aa Gly13-Glu was found in her brother and niece, but there was no evidence in either of the mutation Aa Ser314Cys. While mutation Aa Gly13Glu is responsible for abnormal fibrinopeptide release and prolonged thrombin time, the novel mutation Aa Ser314Cys seems to affect fibrin morphology and fibrinolysis.
Keywords: bodová mutace; Hemorrhagic Disorders; heterozygot; Male; Heterozygote; nesmyslný kodon; posttranslační úpravy proteinů; Afibrinogenemia; Child; Fibrinopeptide A; dítě; Adult; dospělí; Fibrinogens, Abnormal; mužské pohlaví; Protein Processing, Post-Translational; hemoragické poruchy; fibrinogeny abnormální; elektroforéza sérových bílkovin; Point Mutation; fibrin; fibrinopeptid A; lidé; ženské pohlaví; Microscopy, Electron, Scanning; Humans; afibrinogenemie; Codon, Nonsense; Fibrin; Female; mikroskopie elektronová rastrovací; lidé středního věku; Blood Protein Electrophoresis; Middle Aged